Statins improve outcomes of nonsurgical curative treatments in hepatocellular carcinoma patients. Issue 36 (September 2016) - Wu, Li-Li; Hsieh, Mao-Chih; Chow, Jyh-Ming; Liu, Shing-Hwa; Chang, Chia-Lun; Wu, Szu-Yuan
Abstract : Abstract: Statins are associated with a reduced risk of hepatocellular carcinoma (HCC) and have the potential to be an adjuvant agent for HCC. In this study, we examined whether statin use is associated with additional benefits among patients who received curative treatments (CTs) such as surgery, percutaneous ethanol injection (PEI), and radiofrequency ablation (RFA). We conducted a cohort study using the Taiwan National Health Insurance Research Data linked to the Taiwan Cancer Registry in 2001 to 2012. The patient cohort consisted of those who received different treatments, and we compared patients who received statins with those who did not. Statin users were defined as patients who received >28 cumulative defined daily doses after their HCC diagnosis. We used a time-dependent Cox proportional method to model the time from the HCC diagnosis to any death and HCC death between men who received statins and those who did not after adjusting for confounders. Data on statin prescriptions were collected every 6 months to define the user status. In total, 18, 892 patients were included, and the mean follow-up duration was 1.74 years. The adjusted hazard ratio (aHR) of all-cause deaths increased in HCC patients who received RFA/PEI compared to those who received surgery ( P  < 0.0001 and P  < 0.05, with aHRs of 1.81 and 1.16, respectively, for hepatitis B virus [HBV] or non-HBV HCC). However, with the addition of statin use to RFA or PEI, the overall survival was statistically equal. Surgical resection is still superior over other therapies. If HCC patients cannot meet the criteria for surgery, the addition of statin use to RFA or PEI might improve HCC survival.